Народна метеорологя українців Полісся у контексті міжслов’янських зв’язків - Васянович, О. (Народна творчість та етнографія, 2005)
Folk Meteorology is an integral part of the system of knowledge of the inhabitants of Polissya. Polissya is justly evaluated as one of the archaic areas of Slavonic world. It is Polissian statements on material and spiritual culture, language, social and family life, etc., that turn to be a starting point in reconstruction of the most ancient stages in the development of Slavs. Folk experience in weather forecasting has a lot in common with other Slavonic nations. The greatest number of common features is traced in short-termed weather signs. Especially many differences are found in the signs of harvest forecast, that is caused by climatic and economic peculiarities of the development of Slavonic folks.